Evaluation of physicochemical properties of Qinling Apis cerana honey and the antimicrobial activity of the extract against Salmonella Typhimurium LT2 in vitro and in vivo. (1st February 2021) - Wang, Yin; Gou, Xinyi; Yue, Tianli; Ren, Run; Zhao, Haoan; He, Liangliang; Liu, Caiyun; Cao, Wei
Highlights: The VOCs in Qinling Apis cerana honey are more than that in monofloral honeys. Chlorogenic acid in A. cerana honey coule effectively inhibited S . Typhimurium LT2 . The Qinling A. cerana honey could effectively inhibited S . Typhimurium LT2 in vivo . Abstract: Apis cerana honey collected from the Qinling Mountains in China has been widely used for its antimicrobial property in traditional Chinese medicine. However, its antibacterial mechanism against Salmonella Typhimurium LT2 is still uncertain. A total of 52 volatile components were identified using headspace-gas-chromatography-ion-mobility, and Qinling A. cerana honey exhibited more abundant aromas than monofloral honeys. The phenolic extracts of honey sample F exhibited the lowest minimum inhibitory concentration (5 mg/mL), and chlorogenic acid exhibited the highest (155.91 ± 0.79 mg/kg), followed by caffeic acid, and rutin. After being treated with the extract, cell membranes of S. Typhimurium LT2 significantly shrunk and further collapsed. The extract treatment on mice caused a significant decrease in S. Typhimurium LT2, and a dramatic increase in the potential prebiotic Lactobacillus in both the caecum and colon. The results demonstrate that the Qinling A. cerana honey extract could effectively inhibit S. Typhimurium in vitro and in vivo .